Reverse torque evaluation in indexed and nonindexed abutments of Morse Taper implants in a mechanical fatigue test - Martins, Caio Marques (2019)
Background: This experimental study assessed reverse torque of indexed and nonindexed (NI) abutments in Morse Taper (MT) implants in a mechanical fatigue test. Materials and Methods: In this experimental study It was used 37 implants MT and over them installed Pilar Flex abutments (4.8 mm × 6 mm × 1.5 mm). The groups were as follows: Group A used 19 MT implants with a NI Pilar Flex abutment loaded with 32 N/cm and Group B used 18 MT implants with an indexed (IN) Pilar Flex abutment loaded with 20 N/cm. The abutments were tested according to ISO standard 14801/2007. The specimens were installed at 30° from the axial axis and underwent a 133 N load, 4 Hz frequency, and 1,000,000 cycles. Once the test was completed, the reverse torque was provided by an electronic torque meter. Data were submitted to statistical analysis using the t-test for independent samples and paired t-test. The significance level was considered P < 0.05. Results: Results obtained showed that the indexed Pilar Flex abutment had a percentage of torque loss from the initial torque of 49% and the NI Pilar Flex abutment lost 14%. Paired Student's t-tests revealed that for both NI (P < 0.001) and indexed (P < 0.001) abutments, the counter torque values were significantly lower than those applied at the initial torque. Conclusion: According on the methodology used, the NI Pilar Flex abutment was more effective regarding the reverse torque in single-unit implant prostheses versus the indexed Pilar Flex abutment. A greater loosening in the indexed Pilar Flex abutment retaining screw was noted in the reverse torque test, and the Pilar Flex abutment failed to show good outcomes related to the cold welding effect.